PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, PERGANTIAN MANAJEMEN, AUDIT DELAY DAN FINANCIAL DISTRESS TERHADAP AUDITOR SWITCHING - Feby Nurma Aulia; Muyassaroh Muyassaroh (Universitas Trilogi, 2025)
Auditor Switching is a change of auditor carried out by a company both voluntarily and mandatory. Where in accordance with OJK Regulation no. 13 of 2017, the audit period for Public Accountants is a maximum of 3 consecutive years, while for accounting public firm it is based on the results of the audit committee evaluation. This research aims to obtain empirical evidence and analyze the influence of Public Accounting Firm Size, Management Change, Audit Delay, and Financial Distress on Auditor Switching. This research uses secondary data sources originating from financial reports. The number of samples used was 102 data from 17 iron and steel industrial companies for the period 2017-2022 listed on the Indonesian Stock Exchange. The data collection method uses a purposive sampling method with predetermined criteria. This research uses logistic regression analysis to explain the independent and dependent variables. The results of this research show that Public Accounting Firm Size and Audit Delay have a positive effect on auditor switching, while the Management Change and Financial Distress variables have no effect on Auditor Switching.Keywords: Auditor switching; Public Accounting Firm Size; Management Change; Audit Delay; Financial Distress